Peran Kepemimpinan Dalam Meningkatkan Produktifitas Karyawan Toko Alfamart Cabang Sukaharja - Riska, Riska Rahayu; Syifa, Syifa Pramudita Fadila (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
In the current era of globalization, quality and superior human resources are important for a company to be able to compete globally. The existence of a leader in a company or organization is also very much needed to help the company achieve the goals that have been set. The problem in this research is how is the role of leadership in increasing the work productivity of its employees. The purpose of this research is to find out whether the role of leadership can influence and increase employee work productivity. The data collection method used in this study is a qualitative descriptive analysis method. The results of this study indicate that the role of leadership greatly influences the level of work productivity of employees at the Afamart store, Sukaharja branch.